Analisis Resepsi Mahasiswa Surabaya terhadap Konten Lina Mukherjee Makan Babi Diawali Bacaan Bismillah pada Akun Tiktok @lilumukerji - Putri, Cindy Prastia; Arviani, Heidy (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The growing social media in Indonesia has caused social media users in Indonesia to increase very rapidly. Social media users use it as a basic need in finding the latest information that is out there, besides that users also use social media as a medium for entertainment, self-expression, and channeling hobbies or even what they have. One of the social media that is in great demand by the public is tiktok. Tiktok is a platform used by its users to exercise freedom of expression. The purpose of this study was to examine the acceptance of Surabaya students towards the tiktok content Lina Mukherjee eats pork beginning with Bismillah reading on freedom of expression using Stuart Hall's reception theory. This study used a descriptive qualitative approach with audience acceptance method. In-depth interviews and documentation were used as data collection techniques. In accordance with the theory put forward by Stuart Hall, this study obtained results, namely the acceptance of Surabaya students towards the tiktok content Lina Mukherjee eats pork beginning with Bismillah reading in freedom of expression which is divided into two positions, namely the negotiated position and the oppositional position. In expressing ourselves or exercising freedom of expression, we should always pay attention to the norms and regulations of religion, state, culture, customs according to the environment we live in, so as not to cause debate in society. Keywords: Freedom of Expression, Mass Communication, Reception Analysis, Tiktok